1999
DOI: 10.1002/(sici)1097-024x(19990425)29:5<479::aid-spe244>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Object versioning in an ODMG‐compliant object database system

Abstract: In this paper, we describe the design and implementation of the SOP Object Version System which is built upon an object database system, called SOP (SNU ODBMS Platform). SOP is fully compliant with ODMG-93, a standard for object databases proposed by the Object Database Management Group (ODMG). To support object versioning in an ODMG C++ OML (Object Manipulation Language) environment, the SOP Object Version System provides a set of APIs (Application Programming Interfaces) as a class library. One important des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…We can point to the extension of the ODMG object model for composite objects [30], the extension of the object model for supporting time and triggers [7,8], the formalization of an object algebra and semantics for the query language [9,10], the extension of the ODMG object model for managing spatial and historical data of the Tripod data model introduced in [31], the study of the viability of using the ODMG data model as a canonical data model in a multidatabase environment described in [22], the view mechanism proposed in [24] to be used in federated databases using ODMG as a canonical data model and the interface developed in [23] for making the interaction with the ODMG schema repository easier. In addition, many prototypes have been developed using ODMG-compliant databases, such as the object version system built upon an ODMG database described in [32] and the solution to the problem of incrementally maintaining materialized views in ODMG databases put forward in [33].…”
Section: Methodologies Defined On Odmgmentioning
confidence: 99%
“…We can point to the extension of the ODMG object model for composite objects [30], the extension of the object model for supporting time and triggers [7,8], the formalization of an object algebra and semantics for the query language [9,10], the extension of the ODMG object model for managing spatial and historical data of the Tripod data model introduced in [31], the study of the viability of using the ODMG data model as a canonical data model in a multidatabase environment described in [22], the view mechanism proposed in [24] to be used in federated databases using ODMG as a canonical data model and the interface developed in [23] for making the interaction with the ODMG schema repository easier. In addition, many prototypes have been developed using ODMG-compliant databases, such as the object version system built upon an ODMG database described in [32] and the solution to the problem of incrementally maintaining materialized views in ODMG databases put forward in [33].…”
Section: Methodologies Defined On Odmgmentioning
confidence: 99%
“…Soprano also support object versioning in an ODMG C++ OML (Object Manipulation Language) environment through the SOP object version system (Lee & Kim, 1999). Our object version system provides object version facility in ODMG standard and gives a solution for dynamic binding in strongly typed languages like C++.…”
Section: The Persistent Object Class Hierarchymentioning
confidence: 99%
“…In addition to the models described above, we also surveyed various version control models [17][18][19][20][21], which manage versions inside a single product. All those models do not manage inter-DEP relationships.…”
Section: Related Workmentioning
confidence: 99%
“…We surveyed quite a few models for configuration management and version control [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (see section 5 for the discussion of related work), and identified that some of them manage configurations and versions within a single product [6, 8, 10, 13-14, 17-21, 24]. With these models, product management across products such as inter-product change ripple effects management, reference incompleteness management, and identification of correlated products for reuse cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%